Comparative Effectiveness of Transversus Abdominis Plane Blocks in Abdominally Based Autologous Breast Reconstruction: A Systematic Review and Meta-analysis. Issue 6 (December 2020) - Chi, David; Chen, Austin D.; Ha, Austin Y.; Yaeger, Lauren H.; Lee, Bernard T.
Abstract : Background: The abdomen is the most common donor site in autologous microvascular free flap breast reconstruction and contributes significantly to postoperative pain, resulting in increased opioid use, length of stay, and hospital costs. Enhanced Recovery After Surgery (ERAS) protocols have demonstrated multiple clinical benefits, but these protocols are widely heterogeneous. Transversus abdominis plane (TAP) blocks have been reported to improve pain control and may be a key driver of the benefits seen with ERAS pathways. Methods: A systematic review and meta-analysis of studies reporting TAP blocks for abdominally based breast reconstruction were performed. Studies were extracted from 6 public databases before February 2019 and pooled in accordance with the PROSPERO registry. Total opioid use, postoperative pain, length of stay, hospital cost, and complications were analyzed using a random effects model. Results: The initial search yielded 420 studies, ultimately narrowed to 12 studies representing 1107 total patients. Total hospital length of stay (mean difference, −1.00 days; P < 0.00001; I 2 = 81%) and opioid requirement (mean difference, −133.80 mg of oral morphine equivalent; P < 0.00001; I 2 = 97%) were decreased for patients receiving TAP blocks. Transversus abdominis plane blocks were not associated with any significant differences in postoperative complications ( P = 0.66), hospital cost ( P = 0.22), and postoperative pain ( P = 0.86). Conclusions: Optimizing postoperative pain management after abdominally based microsurgical breast reconstruction is invaluable for patient recovery. Transversus abdominis plane blocks are associated with a reduction in length of stay and opioid use, representing a safe and reasonable strategy for decreasing postoperative pain. Abstract : Supplemental digital content is available in the text.